SCREENING OF SOYBEAN GENOTYPES AGAINST MACROPHOMINA PHASEOLINA (Journal of Plant Disease Sciences, 2025)
This study of screening of soybean genotypes against Macrophomina phaseolina causing charcoal rot in soybean is carried out at Regional Research Centre (RRC), Amravati to get the resistant genotypes. Screening is carried out under natural field condition as well as soil sick plot condition. Observations and data is calculated by 0 to 9 scale by percent disease Incidence. Total 10 genotypes are screened in , 2024 that are AMS 2022-1, AMNS 06, AMS 2019-1, AMS 22-16, AMS 22-14, AMS 22-7, AMS 22-2, JS-335, AMS 1001, AMS 100 39. Among all this genotypes 3 are resistant (R) that are AMS 2022-1, AMS 22-2, AMS 100 39, 5genotypes are moderately resistant (MR) that are AMNS 06, AMS 2019-1, AMS 22-16, AMS 22-14, AMS 22-7 and 2 genotypes are highly susceptible (HS) that are JS-335 and AMS 1001. Among all this genotypes AMS 1001 showed 100% mortalityunder all conditions.
Keywords: Charcoal rot, Disease, Macrophomina phaseolina, Soybean.